Perancangan Ulang Fasilitas Tata Letak Perpustakaan Universitas XYZ - Oki Sunardi; Yansen W. Winata; Daniel Daniel (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
The Library is one of the most important media for students. But this time the library The access often encounter obstacles in the process of borrowing books. The access constraint is to wait their turn to borrow books if the number of borrowers more than the number of operators and operators often can not find the book to be borrowed, but the book is available at the library. From the results of these interviews is known that in the process of borrowing constraints caused by the ability to book the service and the current library system, library system is closed. From the initial interview is also known that the university also has plans to improve the service system of the closed library systems (closed system) into an open library system (opened system). Activity Relationship Chart (ARC) is a working relationship map used to plan the inter-group relations in terms of relations activities is method being used in this research. ARC is an ideal technique in planning for linkages between each group of related activities.Keywords: Service Evaluation, Quality Function Deployment